DESIGN OF HELICAL TYPE STEAM GENERATOR FOR EXPERIMENTAL POWER REACTOR - Sunny Ineza Putri; Prihadi Setyo Darmanto; Raden Mohammad Subekti (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2023)
Reaktor Daya EksperimentalÂ (RDE) is a high-temperature gas-cooled reactor (HTGR) for electricity generation, heat generation, and hydrogen production by Batan. Empirical and numerical calculations are needed to strengthen the existing design. The numerical method by computational fluid dynamic (CFD) analyzes temperature distribution and pressure drop along the pipe. The Batan RDE steam generator design has a seven-layer helical pipe model, while this research uses a one-layer helix pipe. In empirical calculations, the heat transfer region has three sections; single-phase liquid, two-phase, and single-phase vapor heat transfer. In numerical calculations, apply the assumption of constant heat flux and constant working fluid properties. The results of empiric calculations data showed that the helical pipe height was 3.98 m, shorter than the Batan design, which is 4.97 m. This considerable difference due to empirical calculations did not cover the safety factor. The results of numerical calculations show that in the single-phase, empiric calculation data were acceptable since the different values of numerical calculations for empiric calculations data were below 10%. Meanwhile, the case of the two-phase numerical calculations is not satisfactory and needs further research to obtain optimal results.